PENGARUH PELAYANAN KEFARMASIAN TERHADAP KEPUASAN PASIEN RAWAT JALAN PESERTA BPJS KESEHATAN DI INSTALASI FARMASI PUSKESMAS SAWAN 2 - Made Dwike Swari Santi (Journal Pharmactive, 2025)
Pharmaceutical services are an essential part of the healthcare system in public health centers (puskesmas), particularly in supporting the success of patient treatment. The Pharmacy Installation at Puskesmas Sawan 2 serves an average of 80–90 outpatients per day, most of whom are BPJS Health participants. However, there are still patient complaints regarding the waiting time for medication services. This study aims to determine the effect of pharmaceutical services on the satisfaction of outpatient BPJS Health participants at the Pharmacy Installation of Puskesmas Sawan 2. This research employed a quantitative method with a cross-sectional design. The sample consisted of 112 respondents selected using purposive sampling. Data were collected through a questionnaire and analyzed using the Spearman correlation test. The results showed a significant but weak correlation in the tangible dimension (p<0.001) and responsiveness (p=0.019), a significant moderate correlation in the assurance (p<0.001) and empathy (p<0.001) dimensions, while the reliability dimension showed no significant correlation (p=0.060). Improving service quality, particularly in terms of responsiveness, is necessary